Current Issues in Knowledge Management 2019
DOI: 10.5772/intechopen.86517
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Human Resource Management with Knowledge Management for Better Organizational Performance: How Human Resource Practices Support Knowledge Management Strategies?

Abstract: Contributing to the HR-approach to knowledge management (KM), this chapter aims at outlining the role of human resource management (HRM) in supporting KM through utilizing the theoretical and empirical literature. The article is divided into two sections. The first section presents various knowledge concepts, KM perspectives and KM strategies. This section ends up by linking these topics in a KM sequential model which helps us to track the philosophical underpinnings and perspectives of each KM strategy. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…This evidence is in line with the stream of research focusing on the strong link between HR and KM (El-Farr and Hosseingholizadeh, 2019). As a “strategic human asset” (Ananthram et al , 2013, p. 456), HR is the pivotal vehicle for knowledge creation, sharing and implementation.…”
Section: Theoretical Background and Conceptual Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…This evidence is in line with the stream of research focusing on the strong link between HR and KM (El-Farr and Hosseingholizadeh, 2019). As a “strategic human asset” (Ananthram et al , 2013, p. 456), HR is the pivotal vehicle for knowledge creation, sharing and implementation.…”
Section: Theoretical Background and Conceptual Modelsupporting
confidence: 90%
“…The role of HR and employees’ well-being as an antecedent of organizational performance has been long investigated (Van De Voorde et al , 2012; Guest, 2017; Mohanty, 2018). In this regard, researchers have found that a shared purpose (Hartnell et al , 2011), interactions, a friendly working environment (El-Farr and Hosseingholizadeh, 2019) and engagement (Mohanty, 2018) are all factors enabling knowledge-sharing processes (Goswami and Agrawal, 2020; Enwereuzor, 2021; Nguyen et al , 2021), leading to higher organizational performance.…”
Section: Theoretical Background and Conceptual Modelmentioning
confidence: 99%
“…Senior managers design the plans and policies for effective knowledge management but successful implementation of the plans and policies usually lies on the shoulders of human resources (Soliman and Spooner, 2000). Several scholars have evaluated the effect of HRM on knowledge management (El-Farr and Hosseingholizadeh, 2019;Gope et al, 2018) but very little explorations have been done to study the effects of knowledge management on HRM (Zaim, 2016). El-Farr and Hosseingholizadeh (2019) have proposed that HRM at the strategic level becomes more effective for organizational outcomes when it is aligned with corporate knowledge management strategies.…”
Section: Knowledge Management Capacity and Strategic Human Resource M...mentioning
confidence: 99%
“…After recruiting and selecting candidates, training and development are the key practices and important step in the human resource management process of the hotel industry. Through training and development practices, employees acquire knowledge, skills and attitude for a specific job (El-Farr & Hosseingholizadeh, 2019). Green Training and development practices educate employees on environment management.…”
Section: Green Training and Developmentmentioning
confidence: 99%